Study on outcome of ischemic stroke patient with atrial fibrillation - Mallick, Achinta Kumar; Ali, Md Ahmed; Kafiluddin, Md; Amin, Md Parvez; Kundu, Pijus Kumar; Alahi, Munzur; Yusuf, Nahid (KYAMC Journal, 2018)
Background: Atrial fibrillation (AF) is a common arrhythmia and a major risk factor for ischemic stroke, especially in the elderly patients. Patients with non-valvular AF have a 5-fold excess risk of stroke recurrence and case-fatality rate. Objectives: This study was to evaluate the prevalence of AF and its influence on prognosis in patients with ischemic stroke. Materials & Methods: Total 125 patients with ischaemic stroke were enrolled in this study. Initially they were divided into two groups by ECG - those with AF and those without AF. They were followed up after one month, three months and six months. Comparison was done between the two groups in term of recurrence, mortality and clinical improvement which were assessed by Modified Rankin Score (MRS). Results: Among 125 patients, 22 patients had AF. Those with AF were more frequently male, aged more than 45 years. Recurrence was significantly higher in AF group during one month follow up (p<0.05). The presence of AF was associated with higher mortality in 3 months (p<0.05) and 6 months (p<0.05) follow up. At 3 months follow up clinical deterioration was noted in 9.1% patient with AF compared to 2.9% patients without AF (p<0.01) and at 6 months follow up clinical deterioration was noted in 18.2% patient with AF compared to 4.9% patients without AF (p<0.01). Conclusion: Patients who had an ischemic stroke with accompanying AF had higher mortality, graver stroke severity, more recurrences and poorer functional status than those without AF. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 8-12